A reapropriação do cinema clássico e do imaginário colonial em tabu, de Miguel Gomes - Santos, Daniel Filipe de Souza (2019)
The present work analyses the movie Tabu (2012), by the portuguese director Miguel Gomes and its proximities with the colonial imaginary widespread by the classical cinema. The movie presents three segments: the prologue which tells the story of an explorer in the midle of the African savannah, the lonely everyday of three women in contemporary Lisbon that deal with the consequences of colonialism, and the return to the past of one of them, through the memory of a forbidden love story in colonial Africa. We will do a film analysis that will look into the way Tabu connects with the elements of classical cinema (the image in black and white, the 4:3 frame, the melodrama references and the partial silent segment) and how, at the same time, it questions this same image (through confluence of temporalities, ironies with the melodrama and a fractured sound design). With the help of the theories of Ismail Xavier and Jacques Aumont on classical cinema; Edgar Morin on imaginary, Walter Benjamin on narrative and memory, Valentim Mudimbe on African colonization; Amaranta César on African cinema and Jacques Rancière on the spectator, we will assemble classical and contemporary movies, from American, European and African cinema, to this analyses, looking into if there is a post-colonial thought in the way Tabu returns to the imaginary of classical and colonial cinema.